Hábitos de sucção versus mordida aberta anterior na dentadura decídua: estudo comparativo em venezuelanos e brasileiros - Cardoso, Andréia Carvalho (2012)
Prolonged sucking of artificial nipples and finger are related to malocclusions. The effects of sucking habits on the prevalence of anterior open bite, in the deciduous dentition, were analyzed in Aragua-Venezuela and São Paulo-Brazil. The Brazilian (N = 1,377) and Venezuelan (N = 809) samples consisted of preschool children aged 3 to 6 years. Habits were investigated by means of questionnaires. Calibrated examiners performed clinical evaluations in Aragua and São Paulo. Data were analyzed by logistic regression (α = 0.05). Among 380 preschool children having anterior open bite, 309 were Brazilians and, among these children, 57.9% had pacifier-sucking habits beyond 3 years of age. However, there was no history of digit-sucking in 91.6% of the Brazilians having anterior open bite. The simultaneous analysis of the effects for sucking habits demonstrated that Brazilians with history of pacifier and digit-sucking habits beyond 3 years of age would have, respectively, 68.5 and 14.5 times more chances of presenting anterior open bite than those children without habits, p < 0.001. In Venezuelans diagnosed with this malocclusion only 1.4% had history of pacifier use beyond 3 years of age. Nonetheless, 28.2% had history of digit-sucking habits beyond 3 years of age, resulting in a greater odds ratio (9.3%; p < 0.001) for anterior open bite in relation to children who did not report this habit. No significant effect was found for bottle-feeding on the prevalence of anterior open bite in the studied samples. However, non-breastfed Venezuelans or those who were breastfed for periods shorter than six months would have a 2.08 higher chance of presenting anterior open bite than children who received breastfeeding for six months or longer, p = 0.008. It may be concluded that non-nutritive sucking habits demonstrated predominant effects on the prevalence of anterior open bite. The effect of pacifier use was more evident for Brazilians. In Venezuelans, digit-sucking had a highlighted effect.